2005
DOI: 10.1051/radiopro:2005s1-007
|View full text |Cite
|
Sign up to set email alerts
|

Use of mycorrhizal fungi for the phytostabilisation of radio-contaminated environment (European project MYRRH): Overview on the scientific achievements

Abstract: Abstract. Because plants significantly affect radionuclides (RN) cycling and further dispersion into the biosphere, it is important to understand the biological factors influencing RN plant uptake, accumulation and redistribution. In this respect, mycorrhizal fungi are of particular interest. The effects of ecto-mycorrhizal (ECM) and arbuscular mycorrhizal (AM) fungi on the transport of uranium (U) or radiocaesium (Cs) were investigated both under pot and in vitro culture conditions. Results obtained in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Joner et al (2004) concluded that arbuscular mycorrhizas are unlikely to play any significant role in plant radiocesium acquisition through the process of fungal transport, especially in agricultural ecosystems. However, Dupré de Boulois et al (2005b) suspected that the uptake of radiocesium by AM fungi in this study could have been strongly impaired by the sorption capacity of clay, the bio-availability of K in the soil solution and/or plant K nutritional status.…”
Section: Transport and Immobilization Of Radiocesium By Am Fungimentioning
confidence: 88%
“…Joner et al (2004) concluded that arbuscular mycorrhizas are unlikely to play any significant role in plant radiocesium acquisition through the process of fungal transport, especially in agricultural ecosystems. However, Dupré de Boulois et al (2005b) suspected that the uptake of radiocesium by AM fungi in this study could have been strongly impaired by the sorption capacity of clay, the bio-availability of K in the soil solution and/or plant K nutritional status.…”
Section: Transport and Immobilization Of Radiocesium By Am Fungimentioning
confidence: 88%
“…The inconsistency between these experiments is probably related to the influence of soil constituents and of K on bioavailability of Cs (Delvaux et al ., 2001), root uptake of Cs (Hampton et al ., 2005) and plant accumulation of Cs (Zhu et al ., 2000). Furthermore, transport of Cs by AM fungi, and especially uptake at the level of K/Cs transporters, is probably also influenced by K as hypothesized by Dupré de Boulois and colleagues (2005a). In addition to these physiological aspects, the sterility in the compartmented pot systems could not be guaranteed and the impact of undesirable microorganisms on the bioavailability of Cs could therefore not be excluded.…”
Section: Introductionmentioning
confidence: 92%
“…Studies on the biogeochemical cycle of Cs in forest ecosystems have clearly shown that ectomycorrhizal fungi can accumulate significant amounts of Cs both in their fruiting bodies and in below‐ground mycelium (Nikolova et al ., 1997; Steiner et al ., 2002). In contrast, mycorrhiza‐mediated accumulation and transport of Cs remains uncertain or even controversial in ecosystems dominated by herbaceous plants, which are mainly colonized by AM fungi (Dupré de Boulois et al ., 2005a). Earlier studies suggested that the accumulation of Cs in mycorrhizal plants was either reduced (Dighton and Terry, 1996; Berreck and Haselwandter, 2001), similar (Rogers and Williams, 1986; Rosén et al ., 2005) or increased (McGraw et al ., 1979; Dighton and Terry, 1996; Entry et al ., 1999; Rosén et al ., 2005) as compared with non‐mycorrhizal plants, depending on the plant and AM fungal species considered.…”
Section: Introductionmentioning
confidence: 99%
“…radionuclide uptake by plants (Dupre de Boulois et al, 2008). Nanoparticles became of interest relatively recently, mostly because of their possible use in diverse technologies.…”
Section: Introductionmentioning
confidence: 99%